THE IMPACT OF TRADE OPENNESS AND GOVERNANCE ON FOREIGN DIRECT INVESTMENT: AN ANALYTICAL ECONOMETRIC STUDY FOR SOUTHEAST ASIAN COUNTRIES AND CHINA FOR THE PERIOD (2000-2022) - Shiba, Jyan; Zahir, AbdulHamid (Humanities Journal of University of Zakho, 2024)
The study aims to quantify the impact of trade openness and governance on foreign direct investment in Southeast Asian countries and China during the period 2000-2022. Furthermore, the study utilized the quantitative method, specifically the Autoregressive Distributed Lags Panel Model (ARDL Panel Model, PMG), to determine the impact of the variables under study on foreign direct investment and to estimate the parameters of the model. The findings demonstrate that there is a statistically significant effect of the explanatory variables on foreign direct investment. They indicate that gross domestic products, trade openness and economic stability have a significant positive effect on foreign direct investment of in Southeast Asian countries and China ; while government effectiveness, corruption and exchange rate have a significant negative effect on foreign direct investment of the countries under study. Finally, the study offers a number of proposals, including: the need for host countries to pay attention to the political stability index, which is one of the most influential indicators in attracting foreign investments, since foreign investors inclined to invest in countries where political stability prevails. Additionally, a suitable environment for foreign companies can be created by engaging in free trade agreements and eliminating customs barriers and restrictions for foreign investors.